Desarrollo de un prototipo de corsé personalizado para el tratamiento de escoliosis idiopática en forma de “s” - Bilbao Suárez, Kathleen Jyseth (Universidad Antonio Nariño, 2021)
scoliosis is an abnormal state of the vertebral spine distinguished by a spinal irregularity established in the three spatial dimensions, that is (in the sagittal, coronal and axial directions). It is more commonly defined in adolescent patients, relapsing mainly in the female sex (70%). The objective of this thesis is to show the effectiveness of the rehabilitative treatment through the use of the corset, and offering an alternative in terms of design and functionality to achieve better adherence to treatment.